Race/ethnicity differences in risk and protective factors for marijuana use among U.S. adolescents - Meen Hye Lee; Yeoun Soo Kim-Godwin; Hyungjo Hur (BMC, 2021)
Abstract Background Little is known about how race and ethnicity influence marijuana-specific risk and protective factors in U.S. adolescents. We examined differences in risk and protective factors of marijuana use (MU) and their associations with MU by race/ethnicity. Methods The present study used data from the 2015-2019 National Survey on Drug Use and Health. A total of 68,263 adolescents (aged 12 to 17 years) were divided into seven subgroups by race/ethnicity (White, Hispanic, Black, Asian, Native American, Native Hawaiian/Pacific Islander (NH/PI), and mixed race). Marijuana-specific risk and protective factors (RPFs) were examined, including perceived availability of marijuana, adolescents' perceived risk of MU and perceived disapproval of parents, peers, and close friends. Past-month, past-year, and lifetime MU were used as MU outcomes to examine the associations with RPFs as well as with race/ethnicity. Results Overall, 6.85, 12.67, and 15.52% of the sample reported past-month, past-year, and lifetime MU respectively. Weighted adjusted logistic regression analyses revealed that mixed race adolescents reported the greatest perceived availability of marijuana, whereas Black and Asian adolescents had less access compared to White adolescents. The adolescents' perception of parental disapproval of MU was the lowest for Native American adolescents and highest for Asian adolescents. Mixed race adolescents experienced lower peer and close friend disapproval of MU while Black and Asian adolescents had higher. The MU risk perception was lower in most groups including Black, Hispanic, Native American, and mixed race adolescents, but not in Asian adolescents. Native American adolescents scored the highest on all MU outcomes, whereas Asian adolescents scored the lowest. Perceived availability of marijuana was associated with higher MU in all MU outcomes. Lower disapproval MU perceptions and lower MU risk perceptions were also associated with greater MU. Conclusion These findings suggest there is considerable heterogeneity of marijuana risk and protective factors and MU across race/ethnicity among U.S. adolescents.